Predictive Factors of Palliative Radiotherapy Response and Survival in Patients with Spinal Metastases from Hepatocellular Carcinoma - Choi, Chihwan (Gut Liver, 2015)
BACKGROUND/AIMS: Spinal metastases often severely limit the quality of life by causing severe pain and neurological deficits. The purpose of this study was to evaluate the palliative effect of radiotherapy (RT) for spinal metastases from hepatocellular carcinoma (HCC) and to identify factors predictive of survival in HCC patients with spinal metastases who received RT. METHODS: A retrospective analysis was performed on 192 patients with spinal metastases from HCC who received RT. RESULTS: Of 192 patients with spinal metastases from HCC, an overall pain response to palliative RT occurred in 187 patients (97.4%), with a complete pain response (CR) in 41 patients (21.4%) and a partial response in 151 patients (78.6%). A higher biologically effective dose (BED) and more advanced RT techniques were identified as predictive factors for a CR. The 1- and 2-year overall survival (OS) rates were 18.1% and 6.3%, respectively, and the median survival time was 4.5 months. A long OS was associated with good performance status, controlled primary HCC, absence of extrahepatic metastases, and a higher BED. CONCLUSIONS: RT provided effective palliation for patients with painful spinal metastases from HCC. Our results provide information regarding pain control, survival outcomes, and predictive factors for the prognosis of HCC patients with spinal metastases treated with RT.